The CF-modifying gene EHF promotes p.Phe508del-CFTR residual function by altering protein glycosylation and trafficking in epithelial cells - Stanke, Frauke; Barneveld, Andrea van; Hedtfeld, Silke; Wölfl, Stefan; Becker, Tim; Tümmler, Burkhard (European journal of human genetics, 2014)
The three-base-pair deletion c.1521_1523delCTT (p.Phe508del, F508del) in the cystic fibrosis transmembrane conductance regulator (CFTR) is the most frequent disease-causing lesion in cystic fibrosis (CF). The CFTR gene encodes a chloride and bicarbonate channel at the apical membrane of epithelial cells. Altered ion transport of CFTR-expressing epithelia can be used to differentiate manifestations of the so-called CF basic defect. Recently, an 11p13 region has been described as a CF modifier by the North American CF Genetic Modifier Study Consortium. Selecting the epithelial-specific transcription factor EHF (ets homologous factor) as the likely candidate gene on 11p13, we have genotyped two intragenic microsatellites in EHF to replicate the 11p13 finding in the patient cohort of the European CF Twin and Sibling Study. We could observe an association of rare EHF haplotypes among homozygotes for c.1521_1523delCTT in CFTR, which exhibit a CF-untypical manifestation of the CF basic defect such as CFTR-mediated residual chloride secretion and low response to amiloride. We have reviewed transcriptome data obtained from intestinal epithelial samples of homozygotes for c.1521_1523delCTT in CFTR, which were stratified for their EHF genetic background. Transcripts that were upregulated among homozygotes for c.1521_1523delCTT in CFTR, who carry two rare EHF alleles, were enriched for genes that alter protein glycosylation and trafficking, both mechanisms being pivotal for the effective targeting of fully functional p.Phe508del-CFTR to the apical membrane of epithelial cells. We conclude that EHF modifies the CF phenotype by altering capabilities of the epithelial cell to correctly process the folding and trafficking of mutant p.Phe508del-CFTR.